Is modulating virus virulence by induced systemic resistance realistic?. (May 2015) - Faoro, Franco; Gozzo, Franco
Graphical abstract: Highlights: Systemic acquired resistance against viruses: an uncertain fight with many targets. Induction of resistance to systemic viruses is a difficult task to be achieve. Alternative oxidase and salicylic acid orchestrate defense responses. Post-transcriptional gene silencing: complementary or alternative defense strategy? BTH, chitosan and rhizobacteria may be effective against systemic viruses. Abstract: Induction of plant resistance, either achieved by chemicals (systemic acquired resistance, SAR) or by rhizobacteria (induced systemic resistance, ISR) is a possible and/or complementary alternative to manage virus infections in crops. SAR mechanisms operating against viruses are diverse, depending on the pathosystem, and may inhibit virus replication as well as cell-to-cell and long-distance movement. Inhibition is often mediated by salicylic acid with the involvement of alternative oxidase and reactive oxygen species. However, salicylate may also stimulate a separate downstream pathway, leading to the induction of an additional mechanism, based on RNA-dependent RNA polymerase 1-mediated RNA silencing. Thus, SAR and RNA silencing would closely cooperate in the defence against virus infection. Despite tremendous recent progress in the knowledge of SAR mechanisms, only a few compounds, including benzothiadiazole and chitosan have been shown to reduce the severity of systemic virus disease in controlled environment and, more modestly, in open field. Finally, ISR induction, has proved to be a promising strategy to control virus disease, particularly by seed bacterization with a mixture of plant growth-promoting rhizobacteria. However, the use of any of these treatments should be integrated with cultivation practices that reduce vector pressure by the use of insecticides, or by Bt crops.